Effects of β‐Glucan Content and Pearling of Barley in Diet‐Induced Obese Mice. Issue 6 (15th August 2017) - Aoe, Seiichiro; Ichinose, Yasunori; Kohyama, Noriko; Komae, Kozo; Takahashi, Asuka; Yoshioka, Toji; Yanagisawa, Takashi
Abstract : The effects of the β‐glucan content and pearling of barley on abdominal obesity and the proinflammatory state were investigated in diet‐induced obese mice. Male C57BL/6J mice were randomly divided into four groups and fed either a high‐fat diet containing high‐β‐glucan barley (Beau Fiber [BF]) or a high‐fat diet containing β‐glucan‐free barley (Shikoku‐hadaka 84( bgl ) [BGL]) as whole grain flour or 60% pearled flour for 12 weeks. The weights of mesenteric fat, serum total and low density lipoprotein cholesterol levels, serum insulin and fasting glucose levels, oral glucose tolerance test results, and messenger RNA (mRNA) expression of proinflammatory markers in epididymal fat in both BF groups were significantly lower than those of both BGL groups. The abundance of Bacteroides in both BF groups was significantly higher than that in both BGL groups, whereas the abundance of Clostridium clusters in both BF groups was significantly lower than that in both BGL groups. No significant differences between the whole grain and pearled flours were observed. These results suggest that high‐β‐glucan barley attenuates the progression of abdominal obesity and the proinflammatory state in diet‐induced obese mice compared with β‐glucan‐free barley, possibly by modifying insulin secretion and the microbiota.